Ectoparasites of birds and mammals of Costa Rica 2. Ticks - Tonn, Robert J.; kohls, Glen M.; Arnold, Keith (Revista de Biología Tropical, 1963)
A list is given of the ticks which were collected from vertebrates in Costa Rica.